ChemInform Abstract: Li2C2, a High‐Capacity Cathode Material for Lithium Ion Batteries. Issue 12 (March 2016) - Tian, Na; Gao, Yurui; Li, Yurong; Wang, Zhaoxiang; Song, Xiaoyan; Chen, Liquan
Abstract: Orthorhombic Li2 C2 as a potential cathode material for Li batteries is prepared by spark plasma sintering (SPS) of a 1.07:1 mixture of Li and C powder under vacuum (1.6 x 10 ‐2 Pa, 600 °C, 1 h) followed by a second SPS consolidation step at 300 MPa (350 °C, 2 min).